The safety zone for mini-implant maxillary anchorage in Mongoloids - Wey Mang Chek; Shim Chung Nam; Lee Meng Yit; Jamaluddin Marhazlinda; Ngeow Wei Cheong (Sciendo, 2012)
Aim: This study aimed to establish a safety zone for the placement of mini-implants in the buccal surface between the second maxillary premolar (PM2) and first maxillary molar (M1) of Mongoloids.